Effectiveness of Cengkeh Leaf Extract Ointment (Syzygium Aromaticum L.) on The Number of Fibroblast Cells on Healing of Injection Wistar Walls (Rattus norvegicus) - Poernomo, Hendri; Ma’ruf, Mochammad Taha; Mbiliyora, Paskarani (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: An open wound is a condition where part of the body's tissue has been damaged from its normal state due to sharp or blunt trauma, changes in temperature, chemicals, explosions, electric shock, or animal bites. Clove leaves contain active ingredients such as eugenol, saponins, phenols, steroids, terpenoids, alkaloids, flavonoids, and tannins, as well as essential oils, which have the potential to be anti-inflammatory, antibacterial, and analgesic, inhibiting cell damage and accelerating the healing process in wounds. Materials and Methods: This type of research is an in vivo laboratory experiment with a posttest-only control group design and sample grouping using a Completely Randomized Design (CRD). The treatment was carried out for 5 days by applying it to the mice's backs twice a day, then on the 6th day, decapitation was carried out, taking specimens to observe the number of fibroblast cells. Results and Discussions: The research was analyzed using one-way ANOVA followed by the Least Significant Difference (LSD) test. The results of the study showed that administering cloveleaf extract ointment (Syzygium Aromaticum L.) with concentrations of 3%, 6% and 9% was effective in increasing the number of fibroblast cells in the healing process of incisional wounds on the backs of Wistar rats (Rattus norvegicus). Conclusion: Giving cloveleaf extract ointment at a concentration of 3% is more effective in increasing the number of fibroblast cells in the healing process of incisional wounds in mice compared to concentrations of 6% and 9%.